2012
DOI: 10.1103/physrevd.85.096001
|View full text |Cite
|
Sign up to set email alerts
|

B0B¯0mixing in gauge-Higgs unification

Abstract: We discuss flavor mixing and resulting Flavor Changing Neutral Current (FCNC) in a five dimensional SU (3) color ⊗ SU (3) ⊗ U (1) gauge-Higgs unification. Flavor mixing is realized by the fact that the bulk and brane localized mass terms are not diagonalized simultaneously. As the concrete FCNC processes, we calculate the rate of B

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…s mixings [1,2,3]. In our model, the most dominant contributions to ∆F = 2 FCNC are due to KK gluon exchange at the tree level.…”
Section: Yukawa Hierarchy and Flavor Mixingmentioning
confidence: 84%
See 1 more Smart Citation
“…s mixings [1,2,3]. In our model, the most dominant contributions to ∆F = 2 FCNC are due to KK gluon exchange at the tree level.…”
Section: Yukawa Hierarchy and Flavor Mixingmentioning
confidence: 84%
“…3 The gauge symmetry SU(3) is broken to SU(2) × U(1) by the boundary condition and the electroweak symmetry SU(2) × U (1) is broken to U(1) em by Hosotani mechanism. The Langrangian for fermion is…”
Section: Yukawa Hierarchy and Flavor Mixingmentioning
confidence: 99%
“…With these parameters fixed, wave functions of quarks and leptons are determined. In the present paper, we mostly ignore the flavor mixing in the quark and lepton gauge couplings [14,[82][83][84][85][86][87][88]. It has been shown that the Cabibbo-Kobayashi-Maskawa (CKM) mixing matrix can be incorporated in GHU with naturally suppressed FCNCs (flavor changing neutral currents) [14].…”
Section: A Parameter Setsmentioning
confidence: 99%
“…[110]. Also, a mixing matrix in the quark sector, the Cabibbo-Kobayashi-Maskawa (CKM) mixing matrix [111,112], is introduced by brane interaction terms [77,[113][114][115][116]. We will leave further discussions for future studies.…”
Section: Summary and Discussionmentioning
confidence: 99%